Fetal adverse effects following NSAID or metamizole exposure in the 2nd and 3rd trimester: an evaluation of the German Embryotox cohort - Katarina Dathe; Johanna Frank; Stephanie Padberg; Stefanie Hultzsch; Evelin Beck; Christof Schaefer (BMC, 2022)
Abstract Background Non-steroidal anti-inflammatory drugs (NSAID) are frequently used to treat pain, fever and inflammatory conditions. Due to evidenced fetotoxicity, treatment with NSAID and metamizole should be avoided in the 3rd trimester of pregnancy. There is an ongoing debate on fetotoxic risk of 2nd trimester use which is why we have conducted this study. Methods In this observational cohort study outcome of pregnancies with NSAID and/or metamizole exposure in the 2nd and/or 3rd trimester (study cohort n = 1092) was compared with pregnancies exposed to NSAID and/or metamizole in the 1st trimester only (comparison cohort, n = 1154). The WHO-UMC system was used to assess causality between study medication and study endpoints. Prenatal study endpoints were constriction of ductus arteriosus Botalli, oligohydramnios, late spontaneous abortion (SAB) or stillbirth. Postnatal study endpoints were patent ductus arteriosus (PDA), anomalies of the right heart ventricle, primary pulmonary hypertension (PPHT), and neonatal impairment of kidney function. Results Ductus arteriosus constriction was diagnosed in 5/1092 (0.5%) in the study cohort versus 0/1154 pregnancies in the comparison cohort. In one fetus, ductus arteriosus constriction and oligohydramnios occurred already in the late 2nd trimester after long-term NSAID exposure. Oligohydramnios was diagnosed in 41/1092 (3.8%) in the study cohort versus 29/1154 (2.5%) cases in the comparison cohort [RR, 1.5 (95% CI 0.9-2.4)]. Limited to 2nd trimester, oligohydramnios occurred in 8/904 (0.9%) versus 2/1154 (0.2%) pregnancies [RR, 5.1 (95% CI 1.1-24.0)]. At least in four of the 2nd trimester exposed pregnancies NSAID exposure lasted several weeks. Late SAB or stillbirth occurred in 14/1092 (1.3%) versus 17/1154 (1.5%). Postnatal cardiovascular or renal pathology did not differ between the cohorts. Conclusions NSAID use in the 2nd trimester limited to a few days does not appear to pose a relevant risk. Use for longer periods in the advanced 2nd trimester, however, may cause oligohydramnios and ductus arteriosus constriction similar to effects observed after 3rd trimester use.